2008
DOI: 10.1002/prot.22182
|View full text |Cite
|
Sign up to set email alerts
|

Calcium binding to the purple membrane: A molecular dynamics study

Abstract: The purple membrane (PM) is a specialized membrane patch found in halophilic archaea, containing the photoreceptor bacteriorhodopsin (bR). It is long known that calcium ions bind to the PM, but their position and role remain elusive to date. Molecular dynamics simulations in conjunction with a highly detailed model of the PM have been used to investigate the stability of calcium ions placed at three proposed cation binding sites within bR, one near the Schiff base, one in the region of the proton release group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Nevertheless, the direct relations between the glycolipids and the thermal or salt tolerance of extremophiles have yet to be discovered. Another intriguing coincidence is that many physiological functions of the membranes of extremophiles seem to be related to their bound calcium ions, even though the binding sites and the roles of the ions themselves are unclear4142. We hypothesize that the increased hydration from calcium binding to glycolipids, thus stabilizing the membrane structure, may provide an alternative view for explaining extremophile physiology.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the direct relations between the glycolipids and the thermal or salt tolerance of extremophiles have yet to be discovered. Another intriguing coincidence is that many physiological functions of the membranes of extremophiles seem to be related to their bound calcium ions, even though the binding sites and the roles of the ions themselves are unclear4142. We hypothesize that the increased hydration from calcium binding to glycolipids, thus stabilizing the membrane structure, may provide an alternative view for explaining extremophile physiology.…”
Section: Discussionmentioning
confidence: 94%
“…For a single protein, or none, the optimal unit cell is a hexagonal prism, but for 2–9 optimal arrangements were designed specifically for DAFT (Figure ). These layouts originate from a means of creating enlarged systems of semicrystalline patches, such as the purple membrane, in such a way that the periodic images would be maximally decoupled . We later realized that this could be particularly useful for distributing proteins for studying association, as each layout establishes a fixed separation between any two components, corresponding to equal encounter probabilities.…”
Section: Background and Implementationmentioning
confidence: 99%
“…These layouts originate from a means of creating enlarged systems of semicrystalline patches, such as the purple membrane, in such a way that the periodic images would be maximally decoupled. 34 We later realized that this could be particularly useful for distributing proteins for studying association, as each layout establishes a fixed separation between any two components, corresponding to equal encounter probabilities. This is exemplified in the first two images in Figure 1, which highlight the layouts for two and three protein components.…”
Section: Background and Implementationmentioning
confidence: 99%
“…It is therefore of great interest that molecular dynamics (MD) simulation can provide supplementary insights into structure and dynamics in different environments using either X-ray or NMR structures of membrane proteins as the initial structure. Previous molecular dynamics studies of membrane proteins have been reported describing, among other things, the dynamic behaviour of bacterial b-barrel proteins (Domene et al 2003;Khalid et al 2008), the water transport in aquaporins (Hub and de Groot 2008;Hub et al 2005), the calcium binding in the light harvesting protein bacteriorhodopsin (Wassenaar et al 2009), the molecular mechanisms of tension-dependent channel gating (Colombo et al 2003), and the selectivity mechanisms of ion channels (Shrivastava et al 2002). MD simulation also offers the possibility to compare the dynamics of a membrane protein in the experimental environment, i.e.…”
Section: Introductionmentioning
confidence: 99%